Membangun Masyarakat Tangguh Bencana Melalui Kegiatan Sosialisasi Sadar Bencana Dan Geowisata, Pekon Air Abang, Kec. Ulu Belu, Tanggamus - Destawan, Ridho; Kurniawan, Andri; Hanif, Irfan; Ismail, Muhammad Rizky (Nemui Nyimah, 2024)
The landslide disaster that occurred in Pekon Air Abang and Datarajan, Ulu Belu District, Tanggamus Regency on Friday 24 May 2024 evening has resulted in losses in the form of lives and material. The landslide resulted in a shack being buried under landslide material, causing one victim to be injured and another resident has not been found. Materially, the landslide disaster caused access to the main link from Talang Padang District - Ngarip District to be cut off so that the economy and logistics supplies were disrupted. Apart from that, landslides have caused residents' plantation land to be converted into unproductive land. This research aims to improve and optimize disaster mitigation and geotourism potential in the area through landslide disaster awareness outreach activities, replanting trees, and opening the Asmara Waterfall tourist access route. The result of service activities at Pekon Air Abang is high public awareness regarding disaster mitigation as seen in their participation and enthusiasm in tree planting activities and the opening of the Asmara Waterfall tourist route. Apart from that, Pekon Air Abang has become a target village for further service activities towards a disaster resilient community through education and literacy.